Lymphedema: Surgical and Medical Therapy. (September 2016) - Chang, David W.; Masia, Jaume; Garza, Ramon; Skoracki, Roman; Neligan, Peter C.
Abstract : Background: Secondary lymphedema is a dreaded complication that sometimes occurs after treatment of malignancies. Management of lymphedema has historically focused on conservative measures, including physical therapy and compression garments. More recently, surgery has been used for the treatment of secondary lymphedema. Methods: This article represents the experience and treatment approaches of 5 surgeons experienced in lymphatic surgery and includes a literature review in support of the techniques and algorithms presented. Results: This review provides the reader with current thoughts and practices by experienced clinicians who routinely treat lymphedema patients. Conclusion: The medical and surgical treatments of lymphedema are safe and effective techniques to improve symptoms and improve quality of life in properly selected patients. Abstract : Supplemental Digital Content is available in the Text.